Sources of Han Décor : foreign influence on the han dynasty chinese iconography of paradise - Psarras, Sophia-Karin (JSTOR DDA collection, 2019)
Using archaeological data to examine the development of Han dynasty Chinese art (206 BC-AD 220), this book focusses on the iconography of paradise. Influence from the Chinese Bronze Age is discussed along with a surprisingly profound debt to Greece, the Near East and the steppe.